Interface Control of Ferroelectricity in an SrRuO3/BaTiO3/SrRuO3 Capacitor and its Critical Thickness. Issue 19 (3rd March 2017) - Shin, Yeong Jae; Kim, Yoonkoo; Kang, Sung‐Jin; Nahm, Ho‐Hyun; Murugavel, Pattukkannu; Kim, Jeong Rae; Cho, Myung Rae; Wang, Lingfei; Yang, Sang Mo; Yoon, Jong‐Gul; Chung, Jin‐Seok; Kim, Miyoung; et al.
Abstract : The atomic‐scale synthesis of artificial oxide heterostructures offers new opportunities to create novel states that do not occur in nature. The main challenge related to synthesizing these structures is obtaining atomically sharp interfaces with designed termination sequences. In this study, it is demonstrated that the oxygen pressure ( P O 2 ) during growth plays an important role in controlling the interfacial terminations of SrRuO3 /BaTiO3 /SrRuO3 (SRO/BTO/SRO) ferroelectric (FE) capacitors. The SRO/BTO/SRO heterostructures are grown by a pulsed laser deposition method. The top SRO/BTO interface, grown at high P O 2 (around 150 mTorr), usually exhibits a mixture of RuO2 –BaO and SrO–TiO2 terminations. By reducing P O 2, the authors obtain atomically sharp SRO/BTO top interfaces with uniform SrO–TiO2 termination. Using capacitor devices with symmetric and uniform interfacial termination, it is demonstrated for the first time that the FE critical thickness can reach the theoretical limit of 3.5 unit cells. Abstract : Ferroelectric SrRuO3 /BaTiO3 /SrRuO3 capacitors with atomically sharp interfaces are realized by adjusting pulsed laser deposition growth conditions and altering the thermodynamic surface stability of BaTiO3 . The interface atomic structure is designed to have a symmetric SrO–TiO2 atomic sequence at the top and bottom interfaces, and the resulting ferroelectric capacitor exhibits a robust ferroelectricity down to a thickness of ≈1.4 nm.